Independent Campus Internship Scholarship Selection System with TOPSIS Method - S Sefrika (IJISTECH (International Journal of Information System and Technology), 2022)
Currently, the Ministry of Education, Culture, Research and Technology provides many internship schemes for students from various universities. However, to get there, universities usually conduct internal selections to screen students who are entitled to take part in the internship selection at independent campuses to match their competencies, abilities and talents. There are many ways that can be done, one of which is to determine certain decisions using the TOPSIS method. TOPSIS is ideally used to help solve problems that offer various alternative criteria. TOPSIS helps in the decision-making process. The results showed that the most ideal criterion was a high cumulative achievement index. The results of the research can be used as a reference model in the decision-making process